Telemedicine in Proctology: Modern Approaches (KIUT Publication, 2025)
Telemedicine is a system of providing medical services through remote communication tools between doctors and patients, such as video conferencing, mobile applications, and online consultations. During the COVID-19 pandemic, the global use of telemedicine increased sharply, and this method has now become an integral part of modern medicine.